2010
DOI: 10.1111/j.2041-1014.2009.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal modification of host sugars: a major contributor to colonization of the human airway?

Abstract: Streptococcus pneumoniae colonization of the human airway is an essential precursor for disease; however, the mechanisms by which the bacterium establishes and maintains colonization are poorly understood. It is becoming increasingly clear that S. pneumoniae expresses glycosidases that can modify many glycan structures present in the human airway, including N-linked glycans, O-linked glycans, and glycosaminoglycans. Many of these glycosidases have been shown to contribute to in vivo colonization. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(131 citation statements)
references
References 55 publications
2
128
0
1
Order By: Relevance
“…Bacterial sialidases can have a nutritional function, enabling a bacterium to procure sialic acids from the host for use as carbon and energy sources (13). Sialidases can also function as virulence factors during bacterial pathogenesis, whereby they can contribute to colonization, increase toxin binding, and cause immunomodulatory effects (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Bacterial sialidases can have a nutritional function, enabling a bacterium to procure sialic acids from the host for use as carbon and energy sources (13). Sialidases can also function as virulence factors during bacterial pathogenesis, whereby they can contribute to colonization, increase toxin binding, and cause immunomodulatory effects (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Streptococcus pneumoniae can extensively modify glycans on host cells, and it is thought that this gives pneumococci an advantage during colonization (19). Pneumococci can express up to 10 glycosidases, with one of the most prominent being neuraminidase, which cleaves sialic acid-containing substrates and is expressed by most pneumococcal serotypes (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Streptococcus pneumoniae can extensively modify glycans on host cells, and it is thought that this gives pneumococci an advantage during colonization (19). Pneumococci can express up to 10 glycosidases, with one of the most prominent being neuraminidase, which cleaves sialic acid-containing substrates and is expressed by most pneumococcal serotypes (19,20). Previous reports have shown that neuraminidase A (NanA) is important for the ability of pneumococci to cross the bloodbrain barrier and that neuraminidase activity may contribute to the severity of pneumococcal meningitis (44,45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By deglycosylating human serum components, NanA can interfere with C3 deposition on the pneumococcal surface and reduce opsonophagocytosis by human neutrophils [32]. Moreover, sequential deglycosylation can expose otherwise hidden receptors, such as asialo-GM1, which was shown to act as a receptor for pneumococcal binding to the host epithelium [3335]. NanA, NanB and the presence of sialic acid can contribute to biofilm formation in vitro [3638].…”
Section: Introductionmentioning
confidence: 99%